고압 효소 배양 기술이 백미의 단백질 저감화 효율 및 이화학적 특성에 미치는 효과 - 김채원; 이상윤; 최은정; 류왕보; 홍근표 (한국식품과학회지, 57(3), 2025)
This study was conducted to optimize the hydrolysis efficiency of white rice protein using high-pressure enzymatic incubation and to investigate the physicochemical properties of cooked rice produced from treated white rice. Bromelain was employed as the hydrolyzing enzyme, and the effects of incubation time, enzyme concentration, and substrate concentration on protein hydrolysis were evaluated. The optimal conditions for protein hydrolysis were 200 MPa for 6 h, with an enzyme concentration of 3%. Under these conditions, the protein content was significantly reduced in white rice compared with that in the control. Texture analysis of the cooked rice revealed that low-protein rice exhibited reduced hardness and increased adhesiveness, along with substantial changes in color and appearance. These findings suggest that high-pressure enzymatic incubation is an effective method for protein reduction in rice, offering potential applications in the development of rice products intended for individuals on protein-restricted diets, such as those with kidney disease. KCI Citation Count: 0